Establishing and validating a root water uptake model under the effects of superabsorbent polymers. (12th March 2018) - Liao, Renkuan; Yang, Peiling; Yu, Haoliang; Wu, Wenyong; Ren, Shumei
Abstract: In‐depth understanding of the patterns of root water uptake (RWU) is the key to improving the water‐use efficiency of plants. Superabsorbent polymers (SAPs) can repeatedly absorb and then release water to plants when needed, which substantially increases the water‐use efficiency of plants in arid and semiarid farming. However, it also creates a challenge in modeling RWU due to unstable soil hydraulic parameters and the unclear response of root growth to SAP application. A controlled soil column experiment was conducted to investigate the response of two important root indexes, that is, root length density (RLD) and root nitrogen mass density (RND), to SAP application, as well as their relationships with RWU. The results showed that the use of the SAP caused a steady increase in RND, and it also substantially increased the RLD in the early stage, but the rate of increase gradually slowed over time. The effect of unstable soil hydraulic parameters on RWU was analyzed in a numerical experiment, which indicated that the time‐dependent effect of SAP on soil hydraulic parameters should be considered to avoid errors in calculating RWU. A specific method for calculating the RWU source/sink term in the Richards equation was proposed and ultimately used as the theoretical value of RWU to verify the RWU models based on RLD and RND to ensure the best one was selected. The results showed that RND was better able to be used for development of the RWU model to simulate the patterns of RWU under SAP application.